First part)

Bring all the real terms to the left side of the equation. Bring all imaginary terms to the right side. Also, align all like terms.

2x - 8 = 20i - 4iy eq1

-6x - 2 = - 5i + 10iy eq2

Next, we can multiply eq1 by 3. Keep eq2 as it is.

6x - 24 = 60i - 12iy eq1

-6x - 2 = -5i - 10iy eq2

Add the equations to eliminate the x terms.

-26 = 55i - 22iy

Subtract 55i on both sides of the equation.

-26 - 55i = -22iy

Divide both sides of the equation by -22i.

**(-26 - 55i) / -22i = y**

Then substitute this value of y into eq2 to solve for x. I leave this part to you.

Second part)

conjugate of -3 + i is -3 - i

conjugate of -4 + 3i is -4 - 3i

conjugate of 11i is -11i

Last part)

Set f(x) equal to zero and solve for x. I suggest you use the quadratic formula to sovle for x, since you are likely to have complex roots.

Michael J.

10/04/16